The Development of Mind Mapping Media in Flood Material using ADDIE Model - Sri Adelila Sari; Halimatun Sakdiah (Journal of Education and Learning (EduLearn), 2016)
This study aimed to develop a media mind mapping through ADDIE model in teaching the flooding material. The samples that used were students of class X-3 Madrasah Aliyah (MA) Darul Ulum totaling 30 students. This type of study was the Research and Development (R and D) by using ADDIE models. Data collected by using mind mapping sheets that students' work. Data was analyzed by descriptive statistics. Results of this study found that in developing mind mapping media through five stages, namely: analysis, design, development, implementation and evaluation. The study concluded that the media mind mapping that have been developed and validated could be a viable and effective media used in the learning process.